The TOMO-ETNA experiment: an imaging active campaign at Mt. Etna volcano. Context, main objectives, working-plans and involved research projects - Jesús M. Ibáñez; Janire Prudencio; Alejandro Díaz-Moreno; Domenico Patanè; Giuseppe Puglisi; Birger-Gottfried Lühr; Francisco Carrión; Juan José Dañobeitia; Mauro Coltelli; Francesca Bianco; Edoardo Del Pezzo; Torsten Dahm; et al. (Annals of Geophysics, 2016)
The TOMO-ETNA experiment was devised to image of the crust underlying the volcanic edifice and, possibly, its plumbing system by using passive and active refraction/reflection seismic methods. This experiment included activities both on-land and offshore with the main objective of obtaining a new high-resolution seismic tomography to improve the knowledge of the crustal structures existing beneath the Etna volcano and northeast Sicily up to Aeolian Islands. The TOMO ETNA experiment was divided in two phases. The first phase started on June 15, 2014 and finalized on July 24, 2014, with the withdrawal of two removable seismic networks (a Short Period Network and a Broadband network composed by 80 and 20 stations respectively) deployed at Etna volcano and surrounding areas. During this first phase the oceanographic research vessel “Sarmiento de Gamboa” and the hydro-oceanographic vessel “Galatea” performed the offshore activities, which includes the deployment of ocean bottom seismometers (OBS), air-gun shooting for Wide Angle Seismic refraction (WAS), Multi-Channel Seismic (MCS) reflection surveys, magnetic surveys and ROV (Remotely Operated Vehicle) dives. This phase finished with the recovery of the short period seismic network. In the second phase the Broadband seismic network remained operative until October 28, 2014, and the R/V “Aegaeo” performed additional MCS surveys during November 19-27, 2014. Overall, the information deriving from TOMO-ETNA experiment could provide the answer to many uncertainties that have arisen while exploiting the large amount of data provided by the cutting-edge monitoring systems of Etna volcano and seismogenic area of eastern Sicily.